A high temperature macroscopically flexible inorganic CaYAl3O7:Eu3+ nanofiber luminescent membrane. Issue 19 (29th April 2022) - Wang, Dehua; Chen, Lixiang; Jiang, Longlong; Yu, Yang; Lu, Ye; Li, Hebin; Li, Yang; Meng, Zifei; Su, Qi; Zhang, Yongcheng; Wang, Xiaoxiong
Abstract : A macroscopically flexible inorganic nanofiber functional membrane. Abstract : Traditional functional materials are the mainstream of modern materials science research. Recently, flexible inorganic functional materials have emerged, opening a new area of materials science. Among the multiple flexible inorganic functional materials, flexible inorganic luminescent materials are the most typical ones due to the compatibility between their nanostructure and luminescence, and are the best choice for investigation for new applications in this field. The luminous intensity of flexible inorganic luminescence materials increases with the increase of calcination temperature, but the macroscopic flexibility decreases with the increase of calcination temperature, which leads to the urgent demand of having a flexible inorganic luminescence material with both good macroscopic flexibility and high luminescence. In this paper, the famous inorganic luminous material CaYAl3 O7 :Eu 3+ was successfully prepared by electrospinning into a macroscopically flexible form. The macroscopic flexibility and luminescence of a pure inorganic CaYAl3 O7 :Eu 3+ nanofiber membrane were systematically investigated. After calcining at high temperature, the grain size increases, which is beneficial to luminescence. However, reducing the calcination temperature will further optimize the flexibility of the membrane. At the same calcination temperature, the maximum bending strain of the inorganic CaYAl3 O7 :Eu 3+ nanofiber membrane is about 2.4 times that of the inorganic CaTiO3 :Pr 3+ nanofiber membrane, and the macroscopic flexibility of the inorganic CaYAl3 O7 :Eu 3+ nanofiber membrane is obviously better than that of the inorganic CaTiO3 :Pr 3+ nanofiber membrane. This study provides an idea for the preparation of high-temperature macroscopically flexible inorganic functional materials.